Aqueous static zinc-air battery electrolyte and preparation method and application thereof
By introducing sulfoxide compounds to modify the electrolyte in zinc-air batteries, the reaction pathway is altered, the problem of high charging potential is solved, and the battery energy efficiency is improved while the cost is reduced.
Patent Information
- Application Number
- CN202511090031.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-05
- Publication Date
- 2025-11-04
AI Technical Summary
Existing zinc-air batteries suffer from excessively high charging potentials in practical applications. Current catalyst improvement schemes are costly and ineffective, making it difficult to meet the requirements for large-scale commercial applications.
Traditional aqueous electrolytes are modified with sulfoxide compounds and their derivatives to participate in the positive electrode reaction of zinc-air batteries, converting the four-electron reaction into a two-electron reaction and reducing the charging potential.
The charging potential of zinc-air batteries has been reduced, improving battery energy efficiency. Furthermore, the preparation method is simple and low-cost, showing promising application prospects.
Smart Images

Figure CN120895804A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of aqueous static zinc-air battery electrolyte, and particularly relates to an aqueous static zinc-air battery electrolyte, a preparation method and application thereof. BACKGROUND
[0002] With the increasing environmental pollution and the increasingly severe energy shortage situation, zinc metal-air battery (referred to as zinc-air battery) has attracted extensive attention and in-depth research in the field of energy storage due to its environmental friendliness and high energy density. However, there are technical bottlenecks to be solved in the actual working process of zinc-air battery. Among them, the oxygen evolution reaction of the air positive electrode requires high energy, which directly leads to high charging potential of the battery, which is the main factor limiting the energy efficiency improvement of zinc-air battery technology. In order to overcome this technical problem, the existing technology focuses on developing catalysts with higher catalytic activity to reduce the oxygen catalytic reaction barrier in zinc-air battery, thereby reducing the charging potential of the battery. However, the above method has many drawbacks, such as high cost, complex preparation process, and in practical application, the battery performance improvement effect is not significant, which is difficult to meet the needs of large-scale commercial application, therefore, it is urgent to find an economic and effective solution.
[0003] In the prior art, there are some improvement schemes for battery electrolyte. For example, patent CN113140839A discloses an aluminum-air battery electrolyte, a preparation method and application thereof, which adds an organic solvent dimethyl sulfoxide to the alkaline electrolyte to reduce the activity of free water in the solution, thereby achieving the effect of inhibiting the self-corrosion of the aluminum negative electrode. However, the electrolyte is mainly suitable for the technical field of aluminum-air battery, and the patent does not mention that the dimethyl sulfoxide solvent used can directly participate in the positive electrode reaction process as a reactant, which is essentially different from the technical requirements of zinc-air battery. In addition, the document "The Influence of Dimethyl Sulfoxide as Electrolyte Additive on Anodic Dissolution of Alkaline Zinc-Air Flow Battery (Scientific reports 2019, 9, 1: 14958)" discloses a zinc-air flow battery electrolyte and a preparation method and application thereof, which mainly reveals the key regulation effect of dimethyl sulfoxide on the negative electrode zinc dissolution / deposition process, thereby promoting the improvement of the cycle life of zinc-air flow battery, but it does not show that dimethyl sulfoxide can directly participate in the positive electrode reaction process as a reactant.
[0004] Therefore, a new technical scheme with simple operation, economy and environmental friendliness is urgently needed to effectively improve the energy efficiency of the water series static zinc-air battery and promote its wide application in the field of energy storage. SUMMARY
[0005] To solve the above technical problems, the application provides a water series static zinc-air battery electrolyte, a preparation method and application thereof, a sulfoxide compound and its derivative are used to modify the traditional water series electrolyte, which has the characteristics of simple operation, economy and environmental friendliness, and can effectively solve the technical problem of high charging potential of zinc-air battery, and has great application prospect.
[0006] The application is realized by the following technical scheme:
[0007] The first aspect of the application provides a water series static zinc-air battery electrolyte, the water series static zinc-air battery electrolyte comprises an organic compound, an electrolyte salt and a water series solvent, the organic compound is selected from one or more of dimethyl sulfoxide, dimethyl sulfone, diethyl sulfoxide, diethyl sulfone, cyclobutyl sulfoxide, cyclobutyl sulfone and dibutyl sulfoxide; when the organic compound is a liquid, the volume ratio of the water series solvent and the organic compound is 6:4-9:1; when the organic compound is a solid, the concentration of the organic compound in the water series static zinc-air battery electrolyte is 0.5-10 mol / L; the concentration of the electrolyte salt in the water series static zinc-air battery electrolyte is 0.1-6 mol / L.
[0008] The application utilizes the unsaturated sulfur-oxygen bond of the sulfoxide organic compound or the saturated sulfur-oxygen bond of the sulfone organic compound, so that it can preferentially participate in the positive reaction of the water series static zinc-air battery as a reactant under certain conditions, and compete with the oxygen evolution reaction of the alkali ion (or solvent water) in the electrolyte; therefore, the application can convert the original four-electron reaction in the charging and discharging process into a two-electron reaction, thereby greatly reducing the activation energy in the reaction process, reducing the charging potential and improving the energy efficiency of the battery.
[0009] Further, the organic compound is preferably dimethyl sulfoxide.
[0010] The liquid flow battery system of the prior art and the static zinc-air system of the application have differences in structural design, working principle and use scene, and there is no data to show that the addition of dimethyl sulfoxide can directly participate in the positive reaction, which is essentially different from the design idea of the application that the organic compound participates in the positive reaction of the battery and reduces the charging voltage of the battery.
[0011] Further, the electrolyte salt is selected from one or more of potassium hydroxide, sodium hydroxide, zinc sulfate, zinc chloride, zinc acetate, ammonium chloride, ammonium acetate, sodium chloride and zinc trifluoromethyl sulfonate, and is preferably potassium hydroxide.
[0012] Preferably, the concentration of the electrolyte salt in the aqueous static zinc-air battery electrolyte is 0.1-1 mol / L.
[0013] Further, the aqueous solvent is water.
[0014] Further, when the organic compound is a liquid, the volume ratio of the aqueous solvent to the organic compound is 6:4-9:1; when the organic compound is a solid, the concentration of the organic compound in the aqueous static zinc-air battery electrolyte is 0.5-10 mol / L. When the content of the organic compound gradually increases, the ion transport rate in the electrolyte decreases, resulting in a decrease in the conductivity of the electrolyte, which in turn affects the cycle life, energy conversion efficiency and other electrochemical properties of the battery; when the content of the organic compound is too high, the organic compound may not be soluble in the electrolyte, resulting in the electrolyte being unusable.
[0015] Preferably, when the organic compound is a liquid, the volume ratio of the aqueous solvent to the organic compound is 6:4-8:2, more preferably 7:3-8:2.
[0016] Preferably, when the organic compound is a solid, the concentration of the organic compound in the aqueous static zinc-air battery electrolyte is 0.5-5 mol / L, more preferably 0.5-2 mol / L.
[0017] Preferably, the aqueous static zinc-air battery electrolyte comprises dimethyl sulfoxide, potassium hydroxide and an aqueous solvent. Dimethyl sulfoxide participates in the charging and discharging process as a redox substance in the static zinc-air battery containing a potassium hydroxide solution, forms a competitive relationship with the original charging and discharging reaction process involving oxygen as a redox substance, replaces the original oxidation reaction process, changes the reaction path in the original charging and discharging process, and thus improves the energy conversion efficiency of the aqueous zinc-air battery in the charging and discharging process.
[0018] The second aspect of the present application provides a preparation method of the aqueous static zinc-air battery electrolyte of the first aspect, comprising the following steps: mixing an organic compound and an aqueous solvent to obtain a mixed solvent; dissolving an electrolyte salt in the mixed solvent to obtain the aqueous static zinc-air battery electrolyte.
[0019] In the specific embodiment, the preparation method of the aqueous static zinc-air battery electrolyte comprises the following steps:
[0020] (1) mixing an organic compound and an aqueous solvent in proportion at room temperature, using a stirrer to stir them uniformly to obtain a mixed solvent;
[0021] (2) dissolving an electrolyte salt in the mixed solvent, using a magnetic stirrer to stir thoroughly to obtain the aqueous static zinc-air battery electrolyte.
[0022] The third aspect of the present application provides the application of the aqueous static zinc-air battery electrolyte in the aqueous static zinc-air battery.
[0023] The fourth aspect of the present application provides an aqueous static zinc-air battery, comprising the aqueous static zinc-air battery electrolyte.
[0024] Further, the aqueous static zinc-air battery comprises a positive electrode, a negative electrode and the aqueous static zinc-air battery electrolyte, and the negative electrode is a metal zinc sheet or a composite material containing metal zinc.
[0025] Further, the positive electrode is a carbon cloth loaded with platinum carbon and ruthenium dioxide.
[0026] Further, the preparation method of the positive electrode comprises the following steps: mixing the platinum carbon and the ruthenium dioxide, and then spraying on the carbon cloth to obtain the carbon cloth loaded with the platinum carbon and the ruthenium dioxide.
[0027] Further, the platinum content of the platinum carbon is 10-30%.
[0028] Further, the mass ratio of the platinum carbon and the ruthenium dioxide is (1-3):1.
[0029] Further, the loading amount of the platinum carbon and the ruthenium dioxide on the carbon cloth is 3-5 mg / cm 2 .
[0030] Further, the aqueous static zinc-air battery is a static non-flow battery, comprising a working electrode, a reference electrode, a counter electrode and the aqueous static zinc-air battery electrolyte.
[0031] Further, the reference electrode is a mercury / mercury oxide electrode, and the counter electrode is a carbon rod.
[0032] Further, the working electrode is a carbon cloth loaded with platinum carbon and ruthenium dioxide.
[0033] Further, the preparation method of the working electrode comprises the following steps: mixing the platinum carbon and the ruthenium dioxide, and then spraying on the carbon cloth to obtain the carbon cloth loaded with the platinum carbon and the ruthenium dioxide.
[0034] Further, the platinum content of the platinum carbon is 10-30%.
[0035] Further, the mass ratio of the platinum carbon and the ruthenium dioxide is (1-3):1.
[0036] Further, the loading amount of the platinum carbon and the ruthenium dioxide on the carbon cloth is 3-5 mg / cm 2 .
[0037] The beneficial effects of the present application are:
[0038] 1. The aqueous static zinc-air battery electrolyte provided by the application is modified by introducing an organic compound with a lower price, the organic compound can participate in the positive electrode reaction of the battery and change the traditional reaction path, compared with the traditional alkaline electrolyte, the aqueous static zinc-air battery electrolyte provided by the application can reduce the battery charging potential and maintain the battery discharging potential, thereby reducing the battery charging and discharging potential difference, and improving the utilization rate of zinc negative electrode.
[0039] 2. The preparation method of the aqueous static zinc-air battery electrolyte provided by the application is safe and simple, the raw materials are cheap and easy to obtain, the preparation cost is low, the scale production is easy to realize, the aqueous static zinc-air battery electrolyte prepared has excellent performance, can effectively improve the energy efficiency of the battery, and has good application prospect. BRIEF DESCRIPTION OF DRAWINGS
[0040] Figure 1 The cycle charge-discharge data graph of the aqueous static zinc-air battery constructed for the aqueous static zinc-air battery electrolyte of Example 1, Example 2 and Comparative Example 1.
[0041] Figure 2 The cycle charge-discharge data graph of the aqueous static zinc-air battery constructed for the aqueous static zinc-air battery electrolyte of Example 1, Example 3 and Comparative Example 1.
[0042] Figure 3 The cycle charge-discharge data graph of the aqueous static zinc-air battery constructed for the aqueous static zinc-air battery electrolyte of Example 4, Example 5 and Comparative Example 1.
[0043] Figure 4 The cycle charge-discharge data graph of the aqueous static zinc-air battery constructed for the aqueous static zinc-air battery electrolyte of Example 5, Example 6 and Example 7.
[0044] Figure 5 The cycle charge-discharge data graph of the aqueous static zinc-air battery constructed for the aqueous static zinc-air battery electrolyte of Example 8 and Comparative Example 2.
[0045] Figure 6 The cycle charge-discharge data graph of the aqueous static zinc-air battery constructed for the aqueous static zinc-air battery electrolyte of Example 9 and Comparative Example 3.
[0046] Figure 7 The cycle charge-discharge data graph of the aqueous static zinc-air battery constructed for the aqueous static zinc-air battery electrolyte of Example 10 and Comparative Example 4.
[0047] Figure 8 The cycle charge-discharge data graph of the aqueous static zinc-air battery constructed for the aqueous static zinc-air battery electrolyte of Example 1, Example 4 and Comparative Example 5.
[0048] Figure 9 Cycle charge-discharge data plot of aqueous static zinc-air battery constructed for the electrolyte of aqueous static zinc-air battery of Example 4 and Comparative Example 6.
[0049] Figure 10 Cycle charge-discharge data plot of aqueous static zinc-air battery constructed for the electrolyte of aqueous static zinc-air battery of Example 4 and Comparative Example 7.
[0050] Figure 11 Linear voltammetry plot of aqueous static zinc-air battery constructed for the electrolyte of aqueous static zinc-air battery of Example 4 to 7 and Comparative Example 1.
[0051] Figure 12 Electron transfer number plot of aqueous static zinc-air battery constructed for the electrolyte of aqueous static zinc-air battery of Example 4, Example 11 and Comparative Example 1.
[0052] Figure 13 Solubility profile plot for Example 1, Example 2, Comparative Example 8 and Comparative Example 9.
[0053] Figure 14 Solubility profile plot for Example 12, Example 13, Comparative Example 10 and Comparative Example 11.
[0054] Figure 15 Cycle charge-discharge data plot of aqueous static zinc-air battery constructed for the electrolyte of aqueous static zinc-air battery of Example 4, Comparative Example 1, Comparative Example 12 and Comparative Example 13. DETAILED DESCRIPTION
[0055] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used in the description herein is for describing particular embodiments only and is not intended to be limiting of the application. As used herein, the term "and / or" includes any and all combinations of one or more of the associated listed items.
[0056] The present application provides an aqueous static zinc-air battery electrolyte, the aqueous static zinc-air battery electrolyte comprising an organic compound, an electrolyte salt and an aqueous solvent, the organic compound being selected from one or more of dimethyl sulfoxide, dimethyl sulfone, diethyl sulfoxide, diethyl sulfone, cyclobutyl sulfoxide, cyclobutyl sulfone and dibutyl sulfoxide.
[0057] The aqueous static zinc-air battery electrolyte provided by the application is modified by introducing an organic compound with a low price, the organic compound can participate in the positive electrode reaction of the battery and change the traditional reaction path, compared with the traditional alkaline electrolyte, the four-electron reaction in the charging and discharging process is converted into a two-electron reaction, thereby greatly reducing the activation energy in the reaction process, reducing the charging potential and improving the energy efficiency of the battery.
[0058] In an embodiment of the application, when the organic compound is a liquid, the volume ratio of the aqueous solvent and the organic compound is (1-9):1; when the organic compound is a solid, the concentration of the organic compound in the aqueous static zinc-air battery electrolyte is 0.5-10 mol / L.
[0059] The application provides a preparation method of an aqueous static zinc-air battery electrolyte, comprising the following steps: mixing an organic compound and an aqueous solvent to obtain a mixed solvent; dissolving an electrolyte salt in the mixed solvent to obtain the aqueous static zinc-air battery electrolyte.
[0060] In an embodiment of the application, the preparation method of the aqueous static zinc-air battery electrolyte comprises the following steps:
[0061] (1) mixing the organic compound and the aqueous solvent in proportion at room temperature, stirring them uniformly by using a stirrer to obtain a mixed solvent;
[0062] (2) dissolving the electrolyte salt in the mixed solvent, and stirring it fully by using a magnetic stirrer to obtain the aqueous static zinc-air battery electrolyte.
[0063] The application will be further described in combination with the drawings and specific embodiments, so that those skilled in the art can better understand the application and implement it, but the embodiments are not used as limitations to the application.
[0064] In the following examples, the experimental methods are conventional methods, and the materials, reagents, etc. used are commercially available unless otherwise specified.
[0065] Example 1
[0066] An aqueous static zinc-air battery electrolyte comprises diethyl sulfoxide, potassium hydroxide and water, the volume ratio of water and diethyl sulfoxide is 9:1, and the concentration of potassium hydroxide in the aqueous static zinc-air battery electrolyte is 1 mol / L.
[0067] The preparation method of the aqueous static zinc-air battery electrolyte of Example 1 comprises the following steps:
[0068] (1) mixing water and diethyl sulfoxide in a volume ratio of 9:1 under room temperature conditions, stirring them uniformly with a stirrer to obtain a mixed solvent;
[0069] (2) dissolving potassium hydroxide in the mixed solvent, stirring it thoroughly with a magnetic stirrer to obtain the water-based static zinc-air battery electrolyte, the concentration of potassium hydroxide in the water-based static zinc-air battery electrolyte being 1 mol / L.
[0070] Example 2
[0071] A water-based static zinc-air battery electrolyte, which is basically the same as that of Example 1, with the difference that the volume ratio of water to diethyl sulfoxide is 8:2.
[0072] The preparation method of the water-based static zinc-air battery electrolyte of Example 2 is basically the same as that of Example 1, with the difference that in step (1), water and diethyl sulfoxide are mixed in a volume ratio of 8:2.
[0073] Example 3
[0074] A water-based static zinc-air battery electrolyte, which is basically the same as that of Example 1, with the difference that diethyl sulfoxide is replaced by cyclobutyl sulfoxide.
[0075] The preparation method of the water-based static zinc-air battery electrolyte of Example 3 is basically the same as that of Example 1, with the difference that in step (1), diethyl sulfoxide is replaced by cyclobutyl sulfoxide.
[0076] Example 4
[0077] A water-based static zinc-air battery electrolyte, which comprises dimethyl sulfoxide, potassium hydroxide and water, the volume ratio of water to dimethyl sulfoxide being 9:1, and the concentration of potassium hydroxide in the water-based static zinc-air battery electrolyte being 1 mol / L.
[0078] The preparation method of the water-based static zinc-air battery electrolyte of Example 4 comprises the following steps:
[0079] (1) mixing water and dimethyl sulfoxide in a volume ratio of 9:1 under room temperature conditions, stirring them uniformly with a stirrer to obtain a mixed solvent;
[0080] (2) dissolving potassium hydroxide in the mixed solvent, stirring it thoroughly with a magnetic stirrer to obtain the water-based static zinc-air battery electrolyte, the concentration of potassium hydroxide in the water-based static zinc-air battery electrolyte being 1 mol / L.
[0081] Example 5
[0082] A water-based static zinc-air battery electrolyte, which is basically the same as that of Example 4, except that the volume ratio of water to dimethyl sulfoxide is 8:2.
[0083] The preparation method of the water-based static zinc-air battery electrolyte of Example 5 is basically the same as that of Example 4, except that in step (1), water and diethyl sulfoxide are mixed in a volume ratio of 8:2.
[0084] Example 6
[0085] A water-based static zinc-air battery electrolyte, which is basically the same as that of Example 4, except that the volume ratio of water to dimethyl sulfoxide is 7:3.
[0086] The preparation method of the water-based static zinc-air battery electrolyte of Example 6 is basically the same as that of Example 4, except that in step (1), water and diethyl sulfoxide are mixed in a volume ratio of 7:3.
[0087] Example 7
[0088] A water-based static zinc-air battery electrolyte, which is basically the same as that of Example 4, except that the volume ratio of water to dimethyl sulfoxide is 6:4.
[0089] The preparation method of the water-based static zinc-air battery electrolyte of Example 7 is basically the same as that of Example 4, except that in step (1), water and diethyl sulfoxide are mixed in a volume ratio of 6:4.
[0090] Example 8
[0091] A water-based static zinc-air battery electrolyte, which comprises dimethyl sulfoxide, potassium hydroxide, sodium chloride and water, the volume ratio of water to dimethyl sulfoxide is 8:2, the concentration of potassium hydroxide in the water-based static zinc-air battery electrolyte is 1 mol / L, and the concentration of sodium chloride in the water-based static zinc-air battery electrolyte is 0.1 mol / L.
[0092] The preparation method of the water-based static zinc-air battery electrolyte of Example 8 comprises the following steps:
[0093] (1) water and dimethyl sulfoxide are mixed in a volume ratio of 8:2 at room temperature, and a stirrer is used to stir them uniformly to obtain a mixed solvent;
[0094] (2) potassium hydroxide and sodium chloride are dissolved in the mixed solvent, and a magnetic stirrer is used to stir them thoroughly to obtain the water-based static zinc-air battery electrolyte, the concentration of potassium hydroxide in the water-based static zinc-air battery electrolyte is 1 mol / L, and the concentration of sodium chloride in the water-based static zinc-air battery electrolyte is 0.1 mol / L.
[0095] Example 9
[0096] A water-based static zinc-air battery electrolyte, which is basically the same as that of Example 8, except that the concentration of sodium chloride in the water-based static zinc-air battery electrolyte is 0.5 mol / L.
[0097] The preparation method of the water-based static zinc-air battery electrolyte of Example 9 is basically the same as that of Example 8, except that in step (2), the concentration of sodium chloride in the water-based static zinc-air battery electrolyte is 0.5 mol / L.
[0098] Example 10
[0099] A water-based static zinc-air battery electrolyte, which is basically the same as that of Example 8, except that the concentration of sodium chloride in the water-based static zinc-air battery electrolyte is 1 mol / L.
[0100] The preparation method of the water-based static zinc-air battery electrolyte of Example 10 is basically the same as that of Example 8, except that in step (2), the concentration of sodium chloride in the water-based static zinc-air battery electrolyte is 1 mol / L.
[0101] Example 11
[0102] A water-based static zinc-air battery electrolyte, which comprises dimethyl sulfone, potassium hydroxide and water, the concentration of potassium hydroxide in the water-based static zinc-air battery electrolyte is 1 mol / L, and the concentration of dimethyl sulfone in the water-based static zinc-air battery electrolyte is 1.4 mol / L.
[0103] The preparation method of the water-based static zinc-air battery electrolyte of Example 11 comprises the following steps:
[0104] (1) mixing water and dimethyl sulfone at room temperature, and stirring them uniformly by using a stirrer to obtain a mixed solvent;
[0105] (2) dissolving potassium hydroxide in the mixed solvent, and stirring it sufficiently by using a magnetic stirrer to obtain the water-based static zinc-air battery electrolyte, the concentration of potassium hydroxide in the water-based static zinc-air battery electrolyte is 1 mol / L, and the concentration of dimethyl sulfone in the water-based static zinc-air battery electrolyte is 1.4 mol / L.
[0106] Example 12
[0107] A water-based static zinc-air battery electrolyte, which is basically the same as that of Example 4, except that the concentration of potassium hydroxide is 6 mol / L.
[0108] Example 13
[0109] A water-based static zinc-air battery electrolyte, which is basically the same as that of Example 5, except that the concentration of potassium hydroxide is 6 mol / L.
[0110] Comparative Example 1
[0111] A water-based static zinc-air battery electrolyte, which comprises potassium hydroxide and water, the concentration of potassium hydroxide in the water-based static zinc-air battery electrolyte being 1 mol / L.
[0112] Comparative Example 2
[0113] A water-based static zinc-air battery electrolyte, which comprises potassium hydroxide, sodium chloride and water, the concentration of potassium hydroxide in the water-based static zinc-air battery electrolyte being 1 mol / L, and the concentration of sodium chloride in the water-based static zinc-air battery electrolyte being 0.1 mol / L.
[0114] Comparative Example 3
[0115] A water-based static zinc-air battery electrolyte, which comprises potassium hydroxide, sodium chloride and water, the concentration of potassium hydroxide in the water-based static zinc-air battery electrolyte being 1 mol / L, and the concentration of sodium chloride in the water-based static zinc-air battery electrolyte being 0.5 mol / L.
[0116] Comparative Example 4
[0117] A water-based static zinc-air battery electrolyte, which comprises potassium hydroxide, sodium chloride and water, the concentration of potassium hydroxide in the water-based static zinc-air battery electrolyte being 1 mol / L, and the concentration of sodium chloride in the water-based static zinc-air battery electrolyte being 1 mol / L.
[0118] Comparative Example 5
[0119] A water-based static zinc-air battery electrolyte, which is basically the same as that of Example 1, except that diethyl sulfoxide is replaced by ethanol, and the volume ratio of water to ethanol is 9:1.
[0120] Comparative Example 6
[0121] A water-based static zinc-air battery electrolyte, which is basically the same as that of Example 1, except that diethyl sulfoxide is replaced by ethylene glycol, and the volume ratio of water to ethylene glycol is 9:1.
[0122] Comparative Example 7
[0123] A water-based static zinc-air battery electrolyte, which is basically the same as that of Example 1, except that diethyl sulfoxide is replaced by urea, and the volume ratio of water to urea is 9:1.
[0124] Comparative Example 8
[0125] An aqueous static zinc-air battery electrolyte is basically the same as that in Example 1, except that the volume ratio of water to diethyl sulfoxide is 4:6.
[0126] Comparative Example 9
[0127] An aqueous static zinc-air battery electrolyte is basically the same as that in Example 1, except that the volume ratio of water to diethyl sulfoxide is 3:7.
[0128] Comparative Example 10
[0129] An aqueous static zinc-air battery electrolyte is basically the same as that in Example 6, except that the concentration of potassium hydroxide is 7 mol / L.
[0130] Comparative Example 11
[0131] An aqueous static zinc-air battery electrolyte is basically the same as that in Example 7, except that the concentration of potassium hydroxide is 7 mol / L.
[0132] Comparative Example 12
[0133] An aqueous static zinc-air battery electrolyte is basically the same as that in Example 4, except that the volume ratio of water to dimethyl sulfoxide is 9.5:0.5.
[0134] Comparative Example 13
[0135] An aqueous static zinc-air battery electrolyte is basically the same as that in Example 4, except that the volume ratio of water to dimethyl sulfoxide is 5:5.
[0136] Test Example 1
[0137] Using a zinc sheet as the negative electrode, the loading is 4 mg / cm³. 2 A platinum-loaded carbon (containing 20% platinum) and ruthenium dioxide-loaded carbon cloth (with a mass ratio of 1:1 of platinum-carbon and ruthenium dioxide) were used as positive electrodes. Aqueous static zinc-air batteries were constructed with the electrolytes of Examples 1-10 and Comparative Examples 1-7, respectively, and their electrochemical performance was tested.
[0138] Test results are as follows Figures 1-10 As shown, from Figures 1-7 As can be seen from this, at a current density of 2 mA / cm² 2In comparison, the potential difference required for cyclic charge-discharge of the aqueous static zinc-air batteries constructed with the electrolytes of Examples 1-4 was all above 700 mV. In contrast, the potential differences required for cyclic charge-discharge of the aqueous static zinc-air batteries constructed with the electrolytes containing diethyl sulfoxide, cyclobutyl sulfoxide, and dimethyl sulfoxide in the examples were approximately 520 mV, 300 mV, and 270 mV, respectively, significantly lower than the charge-discharge potential differences of the aqueous static zinc-air batteries in the comparison examples. This indicates that the addition of these sulfoxide or sulfone organic compounds alters the original four-electron reaction pathway at the positive electrode during battery charging to a two-electron reaction pathway, lowering the energy barrier required for the reaction and thus reducing the reaction potential difference. Figure 8 As can be seen, the cyclic charge-discharge potential difference of the aqueous static zinc-air battery constructed with the aqueous static zinc-air battery electrolyte (KOH electrolyte containing ethanol) in Comparative Example 5 is approximately 560 mV, which is higher than the cyclic charge-discharge potential differences of the aqueous static zinc-air batteries constructed with diethyl sulfoxide and dimethyl sulfoxide electrolytes in Examples 1 and 4, respectively. Figure 9 As can be seen, the cyclic charge-discharge potential difference of the aqueous static zinc-air battery constructed with the aqueous static zinc-air battery electrolyte (KOH electrolyte containing ethylene glycol) in Comparative Example 6 is approximately 640 mV, which is higher than the cyclic charge-discharge potential difference of the aqueous static zinc-air battery constructed with the aqueous static zinc-air battery electrolyte containing dimethyl sulfoxide in Example 4. Figure 10 As can be seen, the cyclic charge-discharge potential difference of the aqueous static zinc-air battery constructed with the aqueous static zinc-air battery electrolyte (KOH electrolyte containing urea) in Comparative Example 7 is about 540mV, which is higher than the cyclic charge-discharge potential difference of the aqueous static zinc-air battery constructed with the aqueous static zinc-air battery electrolyte containing dimethyl sulfoxide in Example 4.
[0139] Test Example 2
[0140] With a loading capacity of 4 mg / cm 2 A platinum-carbon (20% platinum content) and ruthenium dioxide-supported carbon cloth (platinum-carbon and ruthenium dioxide mass ratio of 1:1) was used as the working electrode, a carbon rod as the counter electrode, and a mercury / mercury oxide electrode as the reference electrode. Aqueous static zinc-air batteries were constructed with the electrolytes of Examples 4-7 and Comparative Example 1, respectively, and their linear voltammetry curves were tested.
[0141] Test results are as follows Figure 11 As shown, at a current density of 10 mA / cm² 2 In the example, the charge-discharge potential difference of the aqueous static zinc-air battery constructed with the aqueous static zinc-air battery electrolyte after the addition of methyl sulfoxide was reduced by about 0.25V compared with the charge-discharge potential difference of the aqueous static zinc-air battery in Comparative Example 1.
[0142] Test Example 3
[0143] With a loading capacity of 4 mg / cm 2 A platinum-carbon (20% platinum content) and ruthenium dioxide-supported carbon cloth (1:1 mass ratio of platinum-carbon to ruthenium dioxide) was used as the working electrode, a carbon rod as the counter electrode, and a mercury / mercury oxide electrode as the reference electrode. Aqueous static zinc-air batteries were constructed with the electrolytes of Examples 4, 11, and 1 (Comparative Example 1), respectively, and their electron transfer number curves were tested.
[0144] Test results are as follows Figure 12 As shown, after conversion, the number of electrons transferred in the aqueous static zinc-air battery constructed with the aqueous static zinc-air battery electrolyte added to the example was reduced by 0.25 compared to the aqueous static zinc-air battery of Comparative Example 1. This shows that after adding dimethyl sulfoxide or dimethyl sulfone to the example, some of the original four-electron reactions during the charge and discharge process became two-electron reactions, and the reaction path was changed.
[0145] Test Example 4
[0146] Prepare aqueous static zinc-air battery electrolytes with different potassium hydroxide concentrations and different proportions of organic compounds, and observe their solubility.
[0147] Solubility results as follows Figure 13 and Figure 14 As shown, Figure 13 In an electrolyte with a potassium hydroxide concentration of 1 mol / L, the electrolyte exhibits stratification when the volume ratio of water to diethyl sulfoxide is 4:6 and 3:7. Figure 14 In the electrolyte, when the potassium hydroxide concentration is 7 mol / L, water and dimethyl sulfoxide with a volume ratio of 6:4 and 7:3 exhibit stratification.
[0148] Test Example 5
[0149] Using a zinc sheet as the negative electrode, the loading is 4 mg / cm³. 2 A platinum-loaded carbon (containing 20% platinum) and ruthenium dioxide-loaded carbon cloth (with a mass ratio of 1:1 of platinum-carbon and ruthenium dioxide) was used as the positive electrode. Aqueous static zinc-air batteries were constructed with the electrolytes of Examples 4, 1, 12 and 13, respectively, and their electrochemical performance was tested.
[0150] Test results are as follows Figure 15 As shown, at a current density of 2 mA / cm² 2The potential difference required for the cyclic charge-discharge of the water-based static zinc-air battery constructed by the water-based static zinc-air battery electrolyte of Comparative Example 1, Comparative Example 12 and Comparative Example 13 without dimethyl sulfoxide, with a small amount (volume ratio 9.5:0.5) of dimethyl sulfoxide and with a slightly excessive amount (volume ratio 5:5) of dimethyl sulfoxide was 700 mV, 540 mV and 490 mV, respectively. The potential difference required for the cyclic charge-discharge of the water-based static zinc-air battery constructed by the water-based static zinc-air battery electrolyte of Example 4 with a volume ratio of water and dimethyl sulfoxide of 8:2 was about 270 mV, which was much lower than the potential difference of the charge-discharge of the water-based static zinc-air battery of the Comparative Examples. This indicates that the performance of the battery is not obviously improved after the addition of no, a small amount or an excessive amount of sulfoxide organic compound or sulfone organic compound.
[0151] Obviously, the above-mentioned embodiments of the present application are only examples for clearly illustrating the present application, and are not intended to limit the embodiments of the present application. It should be understood by those skilled in the art that other different forms of changes or variations can be made on the basis of the above description. Here, it is not necessary and also impossible to exhaust all the embodiments. Any modification, equivalent replacement and improvement, etc. made within the spirit and principle of the present application should be included in the protection scope of the claims of the present application.
Claims
1. An aqueous zinc-air cell electrolyte, characterized by, The aqueous static zinc-air battery electrolyte comprises an organic compound, an electrolyte salt and an aqueous solvent, the organic compound is selected from one or more of dimethyl sulfoxide, dimethyl sulfone, diethyl sulfoxide, diethyl sulfone, cyclobutyl sulfoxide, cyclobutyl sulfone and dibutyl sulfoxide; when the organic compound is a liquid, the volume ratio of the aqueous solvent to the organic compound is 6:4-9:1; when the organic compound is a solid, the concentration of the organic compound in the aqueous static zinc-air battery electrolyte is 0.5-10 mol / L; the concentration of the electrolyte salt in the aqueous static zinc-air battery electrolyte is 0.1-6 mol / L.
2. The aqueous zinc-air cell electrolyte of claim 1, wherein, The electrolyte salt is selected from one or more of potassium hydroxide, sodium hydroxide, zinc sulfate, zinc chloride, zinc acetate, ammonium chloride, ammonium acetate, sodium chloride and zinc trifluoromethyl sulfonate.
3. The aqueous zinc-air battery electrolyte of claim 1, wherein, The aqueous solvent is water.
4. A method for producing an aqueous static zinc-air cell electrolyte according to any one of claims 1 to 3, characterized in that The method comprises the following steps: mixing an organic compound and an aqueous solvent to obtain a mixed solvent; dissolving an electrolyte salt in the mixed solvent to obtain the aqueous static zinc-air battery electrolyte.
5. Application of the aqueous static zinc-air battery electrolyte in any one of claims 1-3 in an aqueous static zinc-air battery.
6. An aqueous stationary zinc-air battery, characterized by, The aqueous static zinc-air battery comprises the aqueous static zinc-air battery electrolyte in any one of claims 1-3.
7. The aqueous zinc-air cell of claim 6, wherein, The aqueous static zinc-air battery comprises a positive electrode, a negative electrode and an aqueous static zinc-air battery electrolyte, and the negative electrode is a metal zinc sheet or a composite material containing metal zinc.
8. The aqueous zinc-air cell of claim 6, wherein, The aqueous static zinc-air battery comprises a working electrode, a reference electrode, a counter electrode and an aqueous static zinc-air battery electrolyte.
Citation Information
Patent Citations
Aluminum air battery electrolyte as well as preparation method and application thereof
CN113140839A